2020
DOI: 10.3389/fphys.2020.00209
|View full text |Cite
|
Sign up to set email alerts
|

EDN1-AS, A Novel Long Non-coding RNA Regulating Endothelin-1 in Human Proximal Tubule Cells

Abstract: Endothelin-1 (ET-1) is a peptide hormone that functions as a vasoconstrictor in the vasculature, whereas in the collecting duct of the kidney it exerts blood pressurelowering effects via natriuretic actions. Aberrant ET-1 signaling is associated with several pathological states including hypertension and chronic kidney disease. ET-1 expression is regulated largely through transcriptional control of the gene that encodes ET-1, EDN1. Here we report a long, non-coding RNA (lncRNA) that appears to be antisense to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Among these, only Rorc showed circadian variation of transcript abundance with peak expression at Zeitgeber 20, https://esbl.nhlbi.nih.gov/Databases/Circadian-Prox/). Note, however, prior studies have provided strong evidence for important roles for components of the classical circadian signaling pathway in regulation of various aspects of kidney function (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, only Rorc showed circadian variation of transcript abundance with peak expression at Zeitgeber 20, https://esbl.nhlbi.nih.gov/Databases/Circadian-Prox/). Note, however, prior studies have provided strong evidence for important roles for components of the classical circadian signaling pathway in regulation of various aspects of kidney function (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)49).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have reported significant circadian variability in gene expression in the kidney (17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…EDN1-AS is expressed in multiple human cell types, including the kidneys. In the study by Douma et al (15) in a human kidney proximal tubule cell line (HK-2), the promoter of lncRNA EDN1-AS appeared to have a GRE sequence, which could be recognized and bound by GR, as well as the MR, representing a new mechanism for regulating ET-1 expression. Using CRISPR/Cas9 for the deletion of the GRE element from the EDN1-AS promoter, abolished the binding of GR to EDN1-AS and resulted in increased EDN1-AS expression with a concomitant increase in endothelin 1 expression and cell proliferation.…”
Section: Lncrnas In Glucocorticoid Signalingmentioning
confidence: 99%
“…Furthermore, miRNAs are directly or indirectly influenced by GCs, while it has been shown that the expression level of miRNAs is dependent on endogenous GC levels (13). In addition, long ncRNAs (lncRNAs), such as growth arrest-specific 5 (GAS5) (14) and EDN1-AS (15), regulate the expression levels of GRs, interfering with the GC signaling pathways. It is therefore paramount to increase our understanding of how nc-RNAs, mainly via the action of miRNAs and lncRNAs, regulate GR and are regulated by GCs, building an intricate regulatory network to fine-tune the body's response to various stimuli.…”
Section: Role Of Micrornas and Long Non-coding Rnas In Glucocorticoid...mentioning
confidence: 99%
See 1 more Smart Citation